"The collective circle": Latino immigrant musicians and politics in Charlotte, North Carolina. (May 2014) - BYRD, SAMUEL
ABSTRACT Through their music making, Latino immigrant musicians and audience members in Charlotte, North Carolina, debate political questions relevant to their lives as workers and residents of a globalizing city. Despite contentious politics around immigration, Charlotte's Latino musicians are not active in the organized immigration‐reform movement. Looking at their ambivalent political positionality, I engage with five key themes: how "relationship songs" reveal musicians' personal politics; the effect of everyday policing on immigrant communities and musicians' responses to immigration enforcement policies; the politics of laboring as a Latino musician, including the training and professional ethics that accompany music making; the emergence of musicians as "grassroots intellectuals"; and the importance of the "collective circle"—a frenetic style of band–audience interaction—in helping constitute a sense of agency and shape the informal political stances that Latino musicians take.